Tagging fast neutrons from a 252Cf fission-fragment source. (October 2017) - Scherzinger, J.; Al Jebali, R.; Annand, J.R.M.; Bala, A.; Fissum, K.G.; Hall-Wilton, R.; Hamilton, D.; Mauritzson, N.; Messi, F.; Perrey, H.; Rofors, E.
Abstract: Coincidence and time-of-flight measurement techniques are employed to tag fission neutrons emitted from a 252 Cf source sealed on one side with a very thin layer of Au. The source is positioned within a gaseous 4 He scintillator detector. Together with α particles, both light and heavy fission fragments pass through the thin layer of Au and are detected. The fragments enable the corresponding fission neutrons, which are detected in a NE-213 liquid-scintillator detector, to be tagged. The resulting continuous polychromatic beam of tagged neutrons has an energy dependence that agrees qualitatively with expectations. We anticipate that this technique will provide a cost-effective means for the characterization of neutron-detector efficiency in the energy range 1–6 MeV. Abstract : Highlights: Neutrons emitted from a 252 Cf source with a thin window are tagged using the corresponding fission fragments. The resulting beam of neutrons is continuous and polychromatic. The energy of each neutron is determined via the time-of-flight technique. The approach is anticipated to facilitate cost-effective determinations of neutron-detector efficiencies.